Profile of self-awareness among junior high school students - Lailatussaidah, Lely; Isti'adah, Feida Noor Laila; Nugraha, Agung (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
The purpose of this study was to describe a profile of self-awareness among students in junior high school in the city of Tasikmalaya. Research grounded by the similarities in the tendency of the problems that occur about excessive anxiety among students. The data analysis technique in this study used inferential statistics with random sampling and a total population of 262 students. The results showed that the self-awareness of subject research was in the high category with an average of 75.47%. This shows that most of the subject research have achieved maximum self-awareness in several aspects and indicators, including the achievement of student self-awareness, namely having an understanding of strengths and weaknesses, being able to develop themselves for the desired achievement and have the confidence to voice their opinions.